Penerapan Isak 335 pada Masjid yang Dikelola oleh Pemerintah yang Ada di Kota Bengkulu - Qomariah, Nurul; Abdullah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the problems and obstacles in applying ISAK 335 in the financial reporting of the Bengkulu Government Mosque. The method used is a case study with a qualitative approach. This research collects data through interviews, observations, and documentation studies. The results showed that government-run mosques in Bengkulu City, namely, At-Taqwa Grand Mosque, Baitul Izzah Grand Mosque, and Jamik Mosque have not implemented clear accounting standards and there is no routine supervision from the government and specific regulations regarding mosque financial management. The resulting financial reports are still simple and not by standards, potentially resulting in a lack of transparency and misuse of funds. This study recommends the need for training for mosque administrators, the creation of local regulations on mosque financial management, and regular supervision by the government to improve accountability and public trust. The limitation of this study is the lack of financial report data for two of the three mosques studied, which may affect the analysis results. The findings are expected to be the basis for improvements in mosque financial management in the future.